Financial Reporting Training Based on Financial Accounting Standards for Foundation at Yayasan Darul Hikam Insani Bekasi: Pelatihan Pelaporan Keuangan Berdasarkan Standar Akuntansi Keuangan Yayasan di Yayasan Darul Hikam Insani Bekasi - Jurica Lucyanda; Monica Weni Pratiwi; Berkah Iman Santoso; Raka Muhammad Hasbie; Sarah Novita Asa; Khairun Najwa Mubarok (Institut Riset dan Publikasi Indonesia, 2025)
Community Service (PkM) aims to increase the knowledge and understanding of the management of the Darul Hikam Insani Foundation (YDHI) Pondok Gede Bekasi in compiling the Foundation's financial statements in accordance with the Financial Accounting Standards (SAK) compiled by the Indonesian Institute of Accountants (IAI), namely the Interpretation of Financial Accounting Standards (ISAK) 335. This training was carried out to provide solutions for the management of the Foundation because of the problems faced by the management of the Darul Hikam Insani Mosque Foundation Pondok Gede Bekasi. The problem faced is the limited literacy related to the preparation of financial statements based on Financial Accounting Standards for Foundations which are non-profit oriented entities so that the Foundation's management has not implemented financial reporting based on ISAK 335. Financial statements are a tool of accountability of the Foundation's management to donors so that the finances obtained are reported transparently and accountably. In addition, the rapid development of technology so that it is the focus of this service activity to help and facilitate the Foundation's management to make financial statement applications based on digital-based ISAK 335. This activity provides significant benefits for YDHI management in compiling financial statements based on ISAK 335, in addition to the existence of a digital-based application can help YDHI management prepare transparent and accountable financial reports as a medium of accountability to donors.